2022
DOI: 10.3390/ijms23052613
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Species Rescue of Mutant Phenotype—The Standard for Genetic Analysis of Human Genetic Disorders in Drosophila melanogaster Model

Abstract: Drosophila melanogaster (the fruit fly) is arguably a superstar of genetics, an astonishing versatile experimental model which fueled no less than six Nobel prizes in medicine. Nowadays, an evolving research endeavor is to simulate and investigate human genetic diseases in the powerful D. melanogaster platform. Such a translational experimental strategy is expected to allow scientists not only to understand the molecular mechanisms of the respective disorders but also to alleviate or even cure them. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 280 publications
(233 reference statements)
0
4
0
Order By: Relevance
“…Potentially, doxapram might even serve as a modulator to help alleviate the action of some forms anesthetics if they aid in blocking the same channels. Drosophila , as a model, have immensely served in advancing the understanding of biological systems and currently serve a role in clinically relevant research [ 21 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, doxapram might even serve as a modulator to help alleviate the action of some forms anesthetics if they aid in blocking the same channels. Drosophila , as a model, have immensely served in advancing the understanding of biological systems and currently serve a role in clinically relevant research [ 21 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila as a model organism offers one of the most extensive genetic toolkits available ( Senturk and Bellen, 2018 ) and a nervous system that allows to investigate complex behavior ( Ecovoiu et al, 2022 ). A high conservation rate for human disease-associated genes of ~75% makes it an attractive model to study genetic variants found in humans ( Takai et al, 2020 ).…”
Section: Drosophila Genetics and Tools To Investigate Seizur...mentioning
confidence: 99%
“…To understand the effect of a variant on the phenotype, a rescue experiment can be performed ( Ecovoiu et al, 2022 ). Here, a disease-related phenotype is alleviated by reintroducing a functional allele.…”
Section: Drosophila Genetics and Tools To Investigate Seizur...mentioning
confidence: 99%
“…Numerous studies have documented the utility of such a mimetic approach to demonstrate a human variant's functional impact and inform disease mechanism. [7][8][9][10] Indeed, recent work showed the utility of such a mimetic approach by identifying a gain of function impact for a rare human EZH1 variant in the context of an identical amino acid change in the orthologous E(z) fly gene a fly model. 11 Here, we demonstrate that known pathogenic (P) and LB EED variants faithfully recapitulate their relative function when mimicked in the esc gene, allowing for successful calibration of an assay to test EED VoUS.…”
Section: Introductionmentioning
confidence: 99%